2003
DOI: 10.1038/nature01606
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of oestrogen receptor signalling by association with the activated dioxin receptor

Abstract: Environmental contaminants affect a wide variety of biological events in many species. Dioxins are typical environmental contaminants that exert adverse oestrogen-related effects. Although their anti-oestrogenic actions are well described, dioxins can also induce endometriosis and oestrogen-dependent tumours, implying possible oestrogenic effects. However, the molecular mechanism underlying oestrogen-related actions of dioxins remains largely unknown. A heterodimer of the dioxin receptor (AhR) and Arnt, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
490
7
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(535 citation statements)
references
References 29 publications
20
490
7
2
Order By: Relevance
“…302 A more recent study showed no effect of E2 on 3-methylcholanthrene-inducible AhR activity, but failed to investigate the effects of E2 on HAH-mediated AhRC activity. 229 We have demonstrated that estradiol-activated ERα directly represses AhRC activity at the transcriptional level via tethering to the AhRC in MCF-7 cells. 226 However, others have reported the E2-inducible enhancement of TCDD-dependent CYP1A1 expression in T47D human breast cancer and Huh7 liver cell lines, while having little or no effect in MCF-7 cells.…”
Section: Ahr and Ermentioning
confidence: 82%
“…302 A more recent study showed no effect of E2 on 3-methylcholanthrene-inducible AhR activity, but failed to investigate the effects of E2 on HAH-mediated AhRC activity. 229 We have demonstrated that estradiol-activated ERα directly represses AhRC activity at the transcriptional level via tethering to the AhRC in MCF-7 cells. 226 However, others have reported the E2-inducible enhancement of TCDD-dependent CYP1A1 expression in T47D human breast cancer and Huh7 liver cell lines, while having little or no effect in MCF-7 cells.…”
Section: Ahr and Ermentioning
confidence: 82%
“…The protein composition of these complexes determines the overall transcriptional effect exerted by the receptor (Yanagisawa et al, 2002;Kitagawa et al, 2003;Ohtake et al, 2003). Interaction of retinoid receptors with b-catenin at the Id2 gene WRE presumably leads to recruitment of repressor complexes containing histone deacetylase and demethylase activities.…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of up to 25 mM CH-223191 did not provide a stronger inhibition of pT81/3 Â DRE reporter activity (data not shown). Further, the cells were exposed to 3-MC, which induces DRE reporter activity at this concentration in other models (Ohtake et al, 2003). The pT81/3 Â DRE reporter was inducible by 3-MC in all glioma cell lines tested, as well as in the human astrocytic cell line.…”
Section: Pharmacological and Genetic Modulation Of Ahr Activity In Glmentioning
confidence: 94%